Genomes and Genomics of Nitrogen-fixing Organisms - Palacios, Rafael; Newton, William E.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2005)
This book is the self-contained third volume of a comprehensive series on nitrogen fixation. It presents the state-of-the-art in regards to genomic sciences applied to nitrogen-fixation research. The advent of genomic sciences represents a new era for biology. The classic paradigm based on the gene has now changed to a paradigm that is based on the genome. The knowledge of the complete nucleotide sequence of a genome and its consequences with regard to both transcription and translation lead to an integral and comprehensive view of the biochemistry and physiology of an organism. Moreover, comparative genomic studies provide new insights for a better understanding of the evolutionary process. Nitrogen-fixation research has fully entered the genomics era since the first complete nucleotide sequences of a rhizobial symbiotic plasmid and a methanogenic archaeon were first reported in 1997. Now, the complete nucleotide sequences of many genomes of nitrogen-fixing organism from different taxonomic groups are available. This volume includes chapters devoted to the genomes of specific organisms as well as chapters that cross organismal lines and analyse general aspects centred on functional genomics, genome dynamics, taxonomy, and evolution. No other available work provides the up-to-date and in-depth coverage of this volume, which is intended to serve as an indispensable reference work for academic, governmental, and industrial scientists working in the areas of genomics, transcriptomics, and proteomics, including those studying evolution and taxonomy; to assist students to enter this challenging area of research; and to provide science administrators with ready access to vital relevant information.
Keywords: LIFE SCIENCES; LIFE SCIENCES; LIFE SCIENCES, GENERAL